Assessment of N-(4H-1, 2, 4-triazol-4-yl)octanamide as hydrochloric acid corrosion inhibitor for mild steel. (June 2021) - Mohanty, Ashok; Kumar, Shankar; Tiwari, S.K.
Graphical abstract: Highlights: Corrosion inhibitor N-(4H-1, 2, 4-triazol-4-yl)octanamide (OAT) was synthesized. OAT provides 99.4 % corrosion inhibition on mild steel in 1 M HCl medium. OAT chemisorbs on the mild steel surface to form self-assembled monolayers (SAM). Temperature and immersion time has little impact on the inhibition efficiency of OAT. The corrosion inhibition efficiency can be improved through structural modification. Abstract: The present study demonstrates a method to manipulate the adsorption behavior of corrosion inhibitor molecules through structural modification leading to significant enhancement of the corrosion inhibition efficiency. A weak corrosion inhibitor molecule 4-amino 1, 2, 4 triazole (AT) was structurally modified to N-(4H-1, 2, 4-triazol-4-yl)octanamide (OAT) through the attachment of an octanoyl chain as the hydrophobic tail. Probing of the adsorption behavior of both AT and OAT on mild steel in 1 M HCl using gravimetric, polarization, and electrochemical impedance spectroscopy (EIS) techniques revealed a change of the adsorption mechanism from physisorption to chemisorption due to the structural modification and the corrosion inhibition efficiency improved from 65 % (for 10 mM AT) to 99 % (for 0.3 mM OAT). OAT exhibited a temperature-independent inhibition efficiency of more than 99 % in 30−60 °C range. X-ray photoelectron spectroscopy (XPS) study indicated chemisorption of OAT molecules on the steel surface through nitrogen atoms of the triazole ring, resulting in the formation of a self-assembled monolayer (SAM). Finally, the efficacy of the OAT SAM to protect mild steel from corrosion in HCl medium was demonstrated using scanning electrochemical microscopy (SECM) and scanning electron microscopy (SEM).